Analysis of Cultural and Political Geography Learning Concept Design Based on Case Method and Team-Based Project - Sugiharto, Sugiharto; Rahmadi, M Taufik; Maulia, Tria; Halim, Jennifer; Suciani, Ayu; Rimba, Fellix; Permana, Sendi; Yuniastuti, Eni (Journal of Digital Learning and Education, 2024)
This study investigates the implementation of the Case Method and Team-Based Project learning approaches within the context of the Geography Education Department's cultural and political geography courses at Universitas Negeri Medan. These methods, relevant to the Merdeka Belajar - Kampus Merdeka (MBKM) program, aim to enhance student skills through active, applied learning. Employing a qualitative descriptive approach, the research gathered data via questionnaires distributed through Google Forms to a sample of 67 students out of a total population of 454 from the 2019-2022 academic cohorts. Findings indicate that the duration required for the Case Method varies with the complexity of the cases, ranging from 15-30 minutes for simpler issues to over 60 minutes for more intricate problems. The Team-Based Project approach necessitates 7 to 8 meetings, including initial planning and subsequent implementation phases, monitored by lecturers through direct communication or digital platforms like LMS forums or Zoom channels. However, the study reveals inefficiencies in applying these learning methods within the department, attributed to the substantial workload imposed by the Indonesian National Qualifications Framework (KKNI) and a lack of student engagement in assignments. It suggests a comprehensive revision of IQF assignments towards more discussion-oriented and field-practical approaches to address these challenges.